THE COMPARISON OF EFFECTIVENESS AND SAFETY BETWEEN WARFARIN AND RIVAROXABAN IN HYPERCOAGULATED CENTRAL NERVOUS SYSTEM TUMORS - Sri noviyanty Yusuf; Yunni Diansari; Mediarty Syahrir; Phey Liana (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Abstract:                                                                                                                                           Background: Central nervous system (CNS) tumors originate from the brain and spinal cord, and have complications, such as hypercoagulation. The administration of anticoagulants (warfarin and rivaroxaban) has been able to reduce hypercoagulation-related morbidity and mortality, however, the effectiveness and safety of their use has not been well studied. This study aims to compare the effectiveness and safety of anticoagulant drugs between warfarin and rivaroxaban in hypercoagulated CNS tumors. Methods: This was a randomized clinical trial study, double-blinded, conducted on CNS tumor patients from September-November 2020 at Mohammad Hoesin Hospital. The patients were given warfarin and rivaroxaban for 3 weeks. Coagulation status was measured before and after. Data were analyzed using SPSS ver.24. Results: The mean age of 20 patients was 42.70+8.14 years and majority were female (80%), with tumor characteristics were primary (80%), single (85%), and located in the brain (95%). In the warfarin group (n=10), there were significant improvements in PT (p 0.008), INR (p 0.013), Fibrinogen (p 0.041), and D-Dimer (p 0.008) value, also the rivaroxaban group (n=10) in PT (p 0.013), APTT (p 0.012), INR (p 0.028), Fibrinogen (p 0.047), D-Dimer (p 0.032), and Anti Fxa (p 0.028). However, there was no significant difference between groups, except when comparing the Anti Fxa delta (p 0.041). There was 1 person with major bleeding using warfarin, and 1 person (excluded) with GIT bleeding using rivaroxaban. Conclusion: There was a significant improvement of coagulation value in both groups, also side effects were seen as well. Keyword: CNS Tumor, Hypercoagulation, Warfarin, Rivaroxaban